Representation Of Islam In The TED Talks Youtube Channel And Implementation Of The Cross Culture Understanding Course - Yanah Alfianah (PT. Padang Tekno Corp, 2024)
The aim of the research describes the representation of Islam in America in the TED Talks Youtube Channel video entitled What It's Like to be a Muslim in America. The research are analyzed including obtaining forms of representation of Islam in America, describe the representation of Islam in America and describe the implementation of the Cross Culture Understanding course on the condition of Muslims and Islam in America. The methodology of research utilized to analyze this video is a semiotic structural methodology based on Roland-Barthes theory, that was construct a structured sign system in the format of denotative and connotative signs. After the writer analyzed in the TED Talks Youtube Channel video entitled What It's Like to be a Muslim in America with using denotative and connotative analysis. Finally, the author can describe the inference that Islam representation in America consist of 3 constructions. To describe the representation of Islam in America after the tragedy in America on September 11, 2001 as the shape of Islamophobia, and the results of this research can be implemented with the theories of the Cross Culture Understanding course